PHYTOPLANKTON COMMUNITY STRUCTURE POTENTIALLY ASHARMFUL ALGAL BLOOM (HAB) IN THE WATERS OF PARIAMAN CITY - Nila Sari Lubis; Sofyan Husein Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in Januari 2019 in the waters of Pariaman City. The  purposeof  this  researchwastodeterminethewatersquality, composition, abundance, the structure of phytoplankton community, and to know the correlation (nitrate and phosphate) with the  abundance of phytoplankton  potentially as HAB in Pariaman City waters. This research using a survey method. Location is determined by purposive sampling.The Results of measurements of waters quality parametersshow that temperature29,50-30,75 0C, current speed 0,01-0,07 m/s, brightness 0,86-1,50 m, salinity 28,50-30,50 ppt, pH 7,25-7,50, nitrate concentration 0,0672-0,1010 mg/l andphosphate0,0248-0,0343 mg/l.Totaltypes of phytoplanktonwhich was found 29 species namelyThalassionema sp, Rhizosolenia sp, Pleurosigma sp, Chaetoceros sp, Nitzschia sp, Thalassiosira sp, Lauderia sp, Thalassiothrix sp, Coscinodiscus sp, Bacteriastrum sp, Hemiaulus sp, Guinardia sp, Bacillaria sp, Tabellaria sp, Ceratium sp, Triceratium sp, Pseudo-nitzschia sp, Fragilaria sp, Campylodiscus sp,Ditylum sp, Pyrophacus sp, Pyrocystis sp, Amphisolenia sp, Dinophysis sp, Oscillatoria sp, Trichodesmium sp, Rivularia sp, Licmophora sp, Dictyocha sp. The result of diversity index is 3,37-3,68, dominance indexis 0,11-0,13 anduniformity indexis 0,73-0,77. The average value of phytoplanktonis 68,75x103-190,2x103 sel/m3, that cause the potential for HAB in Pariaman City waters isvery small.The relative abundance of phytoplankton types the potentialHAB isThalassionema sp. The results of linear regression analysisproduce a positive linear relationship with the equation y = 28,905+1388,8x (Nitrate) y = 34,758+3553,5x (phosphate) and the strength of the relationship is classified as strong. Keyword :Phytoplankton, HAB (Harmful Algal Bloom), Abundance, Pariaman